2(7-6(1-n))+6n=14+3(6(n+1)-3n)

Simple and best practice solution for 2(7-6(1-n))+6n=14+3(6(n+1)-3n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(7-6(1-n))+6n=14+3(6(n+1)-3n) equation:


Simplifying
2(7 + -6(1 + -1n)) + 6n = 14 + 3(6(n + 1) + -3n)
2(7 + (1 * -6 + -1n * -6)) + 6n = 14 + 3(6(n + 1) + -3n)
2(7 + (-6 + 6n)) + 6n = 14 + 3(6(n + 1) + -3n)

Combine like terms: 7 + -6 = 1
2(1 + 6n) + 6n = 14 + 3(6(n + 1) + -3n)
(1 * 2 + 6n * 2) + 6n = 14 + 3(6(n + 1) + -3n)
(2 + 12n) + 6n = 14 + 3(6(n + 1) + -3n)

Combine like terms: 12n + 6n = 18n
2 + 18n = 14 + 3(6(n + 1) + -3n)

Reorder the terms:
2 + 18n = 14 + 3(6(1 + n) + -3n)
2 + 18n = 14 + 3((1 * 6 + n * 6) + -3n)
2 + 18n = 14 + 3((6 + 6n) + -3n)

Combine like terms: 6n + -3n = 3n
2 + 18n = 14 + 3(6 + 3n)
2 + 18n = 14 + (6 * 3 + 3n * 3)
2 + 18n = 14 + (18 + 9n)

Combine like terms: 14 + 18 = 32
2 + 18n = 32 + 9n

Solving
2 + 18n = 32 + 9n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-9n' to each side of the equation.
2 + 18n + -9n = 32 + 9n + -9n

Combine like terms: 18n + -9n = 9n
2 + 9n = 32 + 9n + -9n

Combine like terms: 9n + -9n = 0
2 + 9n = 32 + 0
2 + 9n = 32

Add '-2' to each side of the equation.
2 + -2 + 9n = 32 + -2

Combine like terms: 2 + -2 = 0
0 + 9n = 32 + -2
9n = 32 + -2

Combine like terms: 32 + -2 = 30
9n = 30

Divide each side by '9'.
n = 3.333333333

Simplifying
n = 3.333333333

See similar equations:

| -22+2a=-4(1+a) | | -10-5x=11x-8x | | 8-(1+2n)=27+2n | | -3-2x=3x-58 | | (2x^3+3x^2-11x-15)/(2x-5) | | 4(-5n-7)=-7+n | | 5r/2-6=9 | | 4x+2=-7x+2 | | a/5-6=9 | | 2+8(7+x)=83 | | 7(6-6m)=336 | | x^2-2xy+y^2-x=0 | | 6(5-7p)=-264 | | -5+5x=3x-9 | | 252=7(1-5r) | | 3.55+4=22 | | 0.25y+1.5+3=1y-4.5-3 | | x^2+14x-91=4 | | -6(p+8)+4p=-33+3p | | 5-7x=6x+70 | | -4-4v=-3(2v-4) | | -7(v+2)=-14-7v | | 5x-3-3x=3-x | | 495=(x+2)(x)(5) | | -4x-7=2x-49 | | -7+3(3b-5)=-26+8b | | 4(x+3)+7-8x=3 | | 247=2-7(-3-8k) | | 1/3m-7/8=4/9 | | -6x+5=45+4x | | 32+(18-6)/2= | | 1/-7/8=4/9 |

Equations solver categories